El hospital docente del siglo XXI - Dvoredsky, Ana Eugenia; Rosselot Jaramillo., Eduardo (Revista Hospital Clínico Universidad de Chile, 2009)
Since their creation, teaching hospitals been associated to complex health care institutions. They have been able to give education and training to health care professionals while providing patient care. Teaching Hospitals have been the home of medical training in formal and informal curriculum. In the past Century, social and economic changes have resulted in pressure to change the mission of academic medical centers. Educational ranking and quality of care do not always correlate, and the learning process mostly occurs through personal example. Several models have been developed to sustain the academic mission at a time of financial challenge. Still, the need to sustain the basic triad of patient care, teaching and research as the core of the academic mission remains constant.